Impact of EU risk assessment process and administrative regulations for manufacturers of combined hormonal contraceptive prescribing. An analysis of developments in Germany and the implications - Selke Krulichová, Iva; Selke, Gisbert W; Eichler, Uwe; Lappe, Veronika; Godman, Brian; Schubert, Ingrid (Current medical research and opinion, 2019)
OBJECTIVE: Combined hormonal contraceptives (CHC) exhibit differing risks for cardiovascular and thrombotic events (VTE). A European referral process confirmed higher VTE risks for 3rd generation gestagens and drospirenone. CHC are now grouped in risk classes (RC) I, II, and III, with RC III having a higher risk than RC I and X (risk not yet known). Marketing authorization holders were obliged to implement pharmacovigilance measures and risk minimization measures including changes of prescribing information. The study assessed whether these activities induced changes in prescription patterns. METHODS: German prescription data for 1.1 million women below 20 years of age were used to analyze the effects of interventions and potential influence factors using logistic regression. Descriptive statistics were calculated for prescriptions for 3.3 million women from January 2011 to March 2016. RESULTS: Shares of RC I and RC X recipients rose substantially over the observation period, while RC III recipient share showed a steady decrease. The referral induced a slightly faster decrease in RC III and increase in RC X. The implementation of pharmacovigilance measures manifested no additional effect. CONCLUSION: The decrease in RC III share already observed before the referral process can be explained with pre-existing discussions around CHC. The effect attributable to the referral was statistically significant, although very small. While evidence for a connection between interventions and prescription change is only indirect, the study shows that routine data are suitable for impact analyses, and monitoring prescribing patterns can be recommended as feedback after regulatory or political interventions. This is being followed up.
Keywords: lékové předpisy; Drug Prescriptions; Thromboembolism; Intervention analysis; ARIMA; Risk Assessment; Contraceptives, Oral, Combined; Adult; Německo; mladý dospělý; farmaceutický průmysl; Claims data; Young Adult; ženské pohlaví; hodnocení rizik; Drug Industry; Humans; Combined hormonal contraceptives; kontraceptiva orální kombinovaná; Germany; Pharmacoepidemiology; dospělí; Female; lidé